Design and validation of a scale to measure worry for contagion of the COVID-19 (PRE-COVID-19) [Diseño y validación de una escala para medir la preocupación por el contagio de la COVID-19 (PRE-COVID-19)] - Caycho-Rodríguez, Tomás (2020)
ABSTRACT Objective The increase in COVID-19 cases is generating fear and concern in society, which generates an emotional response that influences the adoption of health-related behaviors. The objective of the study is to design and validate the Scale of Worry for Contagion of COVID-19 (PRE-COVID-19). Method The study had a descriptive cross-sectional design. The population were young people and adults who resided in the cities of Lima and Callao (Perú) during the declaration of the national health emergency due to the COVID-19 pandemic, during the period from March 16 to 27, 2020, who were recruited through a non-probability sample. The PRE-COVID-19, the WHO-Five Well-Being Index, the Generalized Anxiety Disorder Scale-2 and a single item were applied to measure the general perception of health. The scales were shared using a Google form through social networks. An internal consistency reliability analysis and structural equation models were performed, specifically confirmatory factor analysis. The recommendations of the Declaration of Helsinki and the principles that guide the ethical practice of online studies were followed. Results Eight hundred and sixteen young people and adults from Lima and Callao (200 men and 616 women; mean age 28.40, SD 7.10) participated. The results show a one-dimensional model with satisfactory goodness-of-fit indices: χ2 (9)=52.00; CFI=0.99; RMSEA=0.09 [0.07, 0.12]; WRMR=0.85. The λ of the model were higher than 0.50 and the reliability had an excellent value (ω=0.90). Likewise, the convergent and discriminant validity is evident between PRE-COVID-19 and measures of anxiety, well-being and self-reported health. Conclusion The results indicate that the PRE-COVID-19 is a valid and reliable instrument to measure concern about the spread of COVID-19 and the emotional impact on people.